c-Met and CREB1 are involved in miR-433-mediated inhibition of the epithelial–mesenchymal transition in bladder cancer by regulating Akt/GSK-3β/Snail signaling - Xu, X (Cell Death Dis, 2016)
Emerging evidence has suggested that microRNAs (miRNAs) have an important role in tumor development and progression by regulating diverse cellular pathways. Here we describe the function and regulation network of miR-433 in bladder cancer (BCa). miR-433 is frequently downregulated in BCa tissues compared with adjacent non-cancerous tissues. Epigenetic mechanisms may be involved in the regulation of miR-433 expression. Enforced expression of miR-433 significantly inhibits proliferation, colony formation, migration, and invasion in BCa cells. In addition, miR-433 inhibits the epithelial–mesenchymal transition (EMT) in BCa cells by regulating c-Met/Akt/GSK-3β/Snail signaling pathway. Both c-Met and CREB1 are downstream target genes of miR-433. CREB1 can also indirectly regulate c-Met/Akt/GSK-3β/Snail signaling via MITF. Furthermore, CREB1 expression is an independent prognostic factor for overall survival in patients with BCa. Finally, there appears to exist a reciprocal regulation between c-Met and miR-433/miR-409-3p. Taken together, this study reveals that miR-433-c-MET/CREB1-Akt/GSK-3β/Snail signaling is critical to EMT in BCa. Targeting the pathway described here may open up new prospects to restrict metastatic progression of BCa.